Reliability study of one TSV based ultra-thin fingerprint sensor package: An improvement of the packaging process - Zhang, Rui (My University, 2019)
Through silicon via (TSV) technology is a vertical electrical interconnection that is etched into a silicon wafer or a die. The primary benefit of using TSV technology is to shortening the interconnection path and further reducing the die thickness. Therefore, the TSV based packages are widely used in fingerprint sensors. In Fingerprint Cards AB (FPC), a new TSV based ultra-thin fingerprint sensor package along with an improvement of the manufacturing process was developed, which enables to further reduce the thickness of the fingerprint sensor package. This thesis report is focused on the reliability study of a newly designed TSV based ultra-thin fingerprint sensor package, to verify and check if it can pass the qualification standards for the consumer electronics products. The new package was designed based on one of the widely-used fingerprint senor package in FPC. A design of experiments (DOE) study regarding the design of the new TSV based ultra-thin fingerprint sensor package was conducted, a set of changes in design parameters were generated according to the requirements of both FPC and the phone original equipment manufacturers (OEMs). The reliability of the new TSV based fingerprint sensor package was analyzed and compared to the reference package by conducting the FEA simulations, such as warpage simulation, ball drop simulation and bending simulation. Based on analysis of the result of the FEA simulations, the TSV based ultra-thin fingerprint sensor has been proved to be qualified to pass the relevant in-house qualification standards of Fingerprint Cards AB, but new studies need to be continued and engineering samples need to be built and test if the phone OEMs want to apply this new TSV based fingerprint sensor to its consumer electronics products.
Keywords: TSV, Packaging design, Process improvement, Fingerprint sensor, DOE